Molecular Identification and Characterization of a Novel Gammaherpesvirus in Wild Rabbits - Fábio A. Abade dos Santos; Ana Duarte; Inês C. Varandas; Silvia S. Barros; Ana M. Henriques; Teresa Fagulha; Margarida D. Duarte (Viruses)
To date, five herpesviruses have been identified in Leporidae (LeHV-1, LeHV-2, LeHV-3, LeHV-4, and LeHV-5). Two of these have been shown to infect the European rabbit (Oryctolagus cuniculus), causing either asymptomatic infection (LeHV-2, a gammaherpesvirus) or virulent disease (LeHV-4, an alphaherpesvirus). Unfortunately, apart from LeHV-4, for which complete genome sequences are available, molecular data on leporid herpesviruses are extremely limited, with no sequences available in public databases for LeHV-1 and LeHV-3, and only a few short sequences for LeHV-2 and LeHV-5. In this study, we investigated the presence of herpesviruses in biological samples from wild rabbits (n = 34) found dead in the field during 2024. A pan-herpesvirus nested PCR directed to the herpesviral DNA polymerase gene was used for screening. Positive samples (n = 14, 41.17%) were further investigated by sequencing analysis of a longer region of the DNA polymerase gene, as well as the glycoprotein B gene and the terminase gene. Blastn analysis of the amplicons revealed the highest similarity to gammaherpesvirus. Phylogenetic analyses based on glycoprotein B, DNA polymerase, and concatenated amino acid sequences consistently placed the newly identified LeHV-6 in close proximity to LeHV-5. Both viruses form a well-supported clade within the Gammaherpesvirinae, clustering with rodent-associated herpesviruses, such as Murine herpesvirus, MuHV-4, and A. sylvaticus rhadinovirus 1. Considering the species susceptibility and the nucleotide similarities with the five previously described leporid herpesviruses, we conclude that a new rabbit gammaherpesvirus has been identified, which we propose to name LeHV-6.